PENGARUH PEMBENTUKAN KELAS IBU NIFAS TERHADAP PENGETAHUAN PADA MASA NIFAS DI WILAYAH KERJA PUSKESMAS PAAL MERAH I KOTA JAMBI - Bayu Arpudi Yanti; Lia Artika Sari; Nurmisih Nurmisih; Ika Murtiyarini (Poltekkes Kemenkes Jambi, 2021)
Background: During the postpartum period, there will be some changes in the body and emotions of the mothers. Various disorders, infections, and myths about taboos about eating certain foods can endanger the life of the mother. This study aimed to determine the effect of postpartum mother class formation on knowledge during the postpartum period in the working area of Paal Merah I Health Center in Jambi City. Methods: This was a pre-experimental design with a one-group pretest and posttest approach. The population in this study was the estimation of postpartum mothers who were supervised under the Paal Merah I Public Health Center, Jambi City in 2020. 20 respondents were selected using an accidental sampling technique. Data analysis was carried out by univariate and bivariate analysis. Results: Some respondents had sufficient and good knowledge before the formation of the postpartum mother class. There was a significant difference between the knowledge of postpartum mothers about the postpartum period before and after being given the formation of a postpartum mother class, indicated by a p-value of 0.008 Conclusion: The formation of the postpartum mother's class was giving influenced by increasing the mother's knowledge about the postpartum period